Criminal liability and responsibility for misconduct in connection with failure to pay contributions for social insurance - Damian Wąsik; Natalia Wąsik; Tomasz Kuczur (Prawo Budżetowe Państwa i Samorządu)
The purpose of this publication is to discuss the nature and causes of irregularities associated with criminal qualification of offense for not paying social security contributions, the issue of guilt evaluation, as well as limitation acts as a consequence of improper criminal qualifications. Presentation of the above. problems should eventually contribute to eliminating errors that may appear in similar cases, it may also help standardize case law. For the purposes of this study was analyzed in detail the course of three selected court proceedings in criminal cases, conducted in the years 2013-2015, concerning non-payment within social security contributions.